The easternmost Middle Paleolithic (Mousterian) from Jinsitai Cave, North China. Issue 114 (January 2018) - Li, Feng; Kuhn, Steven L.; Chen, Fuyou; Wang, Yinghua; Southon, John; Peng, Fei; Shan, Mingchao; Wang, Chunxue; Ge, Junyi; Wang, Xiaomin; Yun, Tala; Gao, Xing
Abstract: The dispersal of Neanderthals and their genetic and cultural interactions with anatomically modern humans and other hominin populations in Eurasia are critical issues in human evolution research. Neither Neanderthal fossils nor typical Mousterian assemblages have been reported in East Asia to date. Here we report on artifact assemblages comparable to western Eurasian Middle Paleolithic (Mousterian) at Jinsitai, a cave site in North China. The lithic industry at Jinsitai appeared at least 47–42 ka and persisted until around 40–37 ka. These findings expand the geographic range of the Mousterian-like industries at least 2000 km further to the east than what has been previously recognized. This discovery supplies a missing part of the picture of Middle Paleolithic distribution in Eurasia and also demonstrates the makers' capacity to adapt to diverse geographic regions and habitats of Eurasia.